Jednokierunkowe Rozciąganie Pierścienia Kołowego - Szelągowski, F. (Engineering Transactions, 1956)
Problems concerning the determination of stress of strain in a circular ring are, in general, more complicated than analogous problems for aninfinite plate with a hole. However, these problems can be solved in some cases in a relatively simple manner. As an example the problem of one-directional tension of a circular ring is considered having a rigid circular inclusion (Fig. 1), and subjected to a tensile load p acting on the periphery of the circle of radius Rθ and uniformly distributed along the diameter.The second example is furnished by the problem of one-directional tension of a circular ring by a load p acting on the outer circle, of radius Rθ, and a load q acting on the inner circle, of radius R (Fig. 3). The equations obtained, determining the values of the stresse Rθ, Rr, θθ, enable also an approximate determination of the stresses in a strip subjected to tension (Figs. 2 and 4), starting from the assumption that the influence of a rigid inclusion or a hole on stress distribution in an infinite plate becomes insignificant beyond a certain region, sufficiently large and bounded in our case by a circle of radius RO.